PELESTARIAN ASYEK MANDI DI TAMAN DI DESA MUKAI HILIR KECAMATAN SIULAK MUKAI KABUPATEN KERINCI - Viola Julia; Desfiarni Desfiarni; Afifah Asriati (FBS Universitas Negeri Padang, 2016)
Abstract The aims of this study is to describe the preservation of the dance ”Asyek Mandi di Taman” in Desa Mukai Hilir, the district of Siulak Mukai, Kerinci by revealing how the preservation was conducted in an effort to develop the dance based on the quantity aspect of the performer(s) of this dance and the quality aspect of its costume development. This survey method applied is qualitative research. Data collection involved library research, observation, interviews, and documentation. The techniques applied in analyzing the data were: collecting the data, categorizing, the data and analyzing the data based on the theory suitable for this study. The data was analyzed in accordance with the problems discussed in this study. The final result was the description of the finding in the form of a report.The results of this study reveals that the numbers of the people involved in the tradition of “Asyek Mandi di Taman” have increased. This can be seen from the expansion of the regions chosen for the performance of “Asyek Mandi di Taman”. Initially, there were only three people involved in this performance however it has reached the total of 24 people now from various villages such as Desa Koto Rendah, Desa Siulak Gedang, Desa Siulak Panjang, Desa Dusun Baru, Pasar Senen, Koto Aro, Lubuk Nagodang, and Mukai Mudik. Similarly, the costumes of the dancers of “Asyek Mandi di Taman” have also developed in terms of the styles of the costumes and how the costumes are worn. The efforts to preserve this dance were evident in the following event such as the “Acara Seni of ISI Padang Panjang on April 30, 2016, the dance was performed in the farewell party of the Mts Siulak District on May 28, 2016, and the “Balemang” event in Desa Siulak, the district of Siulak on June 5, 2016. All the four performances were viewed as successful ones.Key words: Preservation, Asyek Mandi di Taman